2015
DOI: 10.1161/strokeaha.114.006909
|View full text |Cite
|
Sign up to set email alerts
|

Natural History and Management of Basilar Trunk Artery Aneurysms

Abstract: patients were referred to our institution for the management of a cerebral aneurysm (58.3% unruptured and 41.7% ruptured; Figure 1). There were a total Background and Purpose-Basilar trunk aneurysms (BTAs), defined as aneurysms distal to the basilar origin and proximal to the origin of the superior cerebellar artery, are rare and challenging to manage. We describe the natural history and management in a consecutive series of BTAs. Methods-Between 2000 and 2013, 2522 patients with 3238 aneurysms were referred t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
83
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(83 citation statements)
references
References 22 publications
0
83
0
Order By: Relevance
“…BA trunk AN is a relatively rare aneurysm accounting for 1%-2.1% of all cerebral aneurysms 1,2) and causing about 1% of SAH. 1,3) Treatment for BA trunk dissecting AN is very difficult and challenging.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…BA trunk AN is a relatively rare aneurysm accounting for 1%-2.1% of all cerebral aneurysms 1,2) and causing about 1% of SAH. 1,3) Treatment for BA trunk dissecting AN is very difficult and challenging.…”
Section: Discussionmentioning
confidence: 99%
“…From the literature, PAO or stent-assisted incidence of SAH (40%-60%) 3,[6][7][8] and a high mortality rate (17%-79%), 2,[6][7][8][9][10] and the percentage of patients with a favorable outcome is low (25%-33%). [7][8][9] Moreover, the re-bleeding rate is high (19%-86%) in patients who have developed SAH, 2,7,8,10,11) and, once re-bleeding occurs, the mortality rises markedly (70%-90%). [10][11][12] Also, rebleeding is reported to occur frequently within 24 hours after the initial bleeding, 2,5) and prompt prevention of re-bleeding and treatment that maintains a high aneurysm occlusion rate must be evaluated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since male predominance observed in children could not be explained by trauma, it suggests a sex influence on their pathogenesis [26]. Finally, whereas the incidence of SAH in VB IDAs ranges from 61 to 86 % [3,58,68,70,125,171] and 24 % of them rebleed [171], ischemic events associated with the dissections were observed only in 26-62 % of patients [70,150]. In addition, Ono et al [111] reported that 18 % of initially unruptured IDAs showed clinical symptomatic recurrence and 90 % of them had major or minor strokes caused by occlusion of perforating arteries with a mean interval of 8.6 months.…”
Section: Incidencementioning
confidence: 99%
“…Kim et al [69] reported that 100 % of conservatively managed patients with acute BA IDAs experienced rebleeding with the mortality 67 %, while the rest 33 % were only moderately disabled. Interestingly, the chronic BA dissecting aneurysms, also known as chronic mural bleeding ectasias, are diagnosed incidentally in 64 %, as a cause of compressive syndrome or stroke in the remaining 36 % of cases [125]. Even though, these aneurysms have traditionally been considered to follow a benign course without clinical or imaging progression, they may increase in size over time, rupture, or cause a stroke in 25, 4, and 14 % of cases, respectively [125].…”
Section: Prognosismentioning
confidence: 99%